IMPLEMENTATION OF NO SMOKING AREA IN THE CAMPUS AREA POLITEKNIK INDONESIA - Westy Tenriawi (Universitas Islam Negeri Alauddin Makassar, 2022)
Background: The World Health Organization (WHO) has offered a strategy to overcome the problems caused by smoking, namely with six MPOWER